Identify Leading Sectors to Accelerate Regional Economic Growth - Pratama, Umang Wildan (Journal of International Conference Proceedings, 2023)
The establishment of regional autonomy in Indonesia gives greater authority to each region in managing its own government affairs, including in terms of economic development and development. This study aims to analyse the leading sectors of Sleman Regency to determine the direction of regional economic development. This research uses quantitative methods. The data used is secondary data, GRDP for the 2010-2021 period in Sleman Regency, Yogyakarta Special Region Province. In this study, the Location Quotient (LQ) model was used to identify the base and non-base sectors in the Sleman district economy. The assessment of these sectors is based on Gross Regional Domestic Product at constant prices. Klasen typology was used to identify the leading sectors in the regional economy. The results showed that as many as ten sectors in Sleman regency became base sectors during the period 2010-2021. The conclusion from this research is that Sleman Regency has ten leading sectors in the regional economy. Therefore, this research can be used as a reference for the Sleman district government to focus on developing these leading sectors to accelerate economic growth.